Testing the Pediatric Cardiac Quality of Life Inventory in the United Kingdom. (27th November 2012) - Wray, Jo; Franklin, Rodney; Brown, Kate; Cassedy, Amy; Marino, Bradley S
Abstract Aim To establish the validity and reliability of the Pediatric Cardiac Quality of Life Inventory (PCQLI) for children with heart disease in the United Kingdom. Methods Three paediatric cardiac centres recruited patients aged 8–18 years with heart disease. Patient–parent pairs completed a disease‐specific paediatric cardiac quality of life measure (PCQLI), a generic quality of life measure (PedsQL4.0) and behaviour and self‐perception questionnaires. Validity was assessed by correlation of PCQLI scores with heart disease severity, medical care utilization, and PedsQL, behaviour and self‐perception scores, and by correlation of patient and parent PCQLI scores. Reliability was evaluated by administering the PCQLI at two time points. Results The study was completed by 771 patient–parent pairs. Validity was confirmed by the association of lower total PCQLI scores with more complex heart disease and a greater number of hospitalizations and cardiac surgeries (all p < 0.001); moderate to good correlations between patient and parent scores (0.50–0.68); and fair to good correlations between scores for the PCQLI and PedsQL4.0 (0.67–0.77), self‐perception (0.42–0.49) and behaviour measures (0.18–0.62). Test–retest reliability correlations were high (0.72–0.90). Conclusion The PCQLI is a reliable and valid disease‐specific quality‐of‐life measure for children with heart disease in the United Kingdom.